Adaptation of Pramoedya Ananta Toer's Novel Arok Dedes into Concept Art - Baskoro Suryo Banindro; Asnar . Zacky; Rikhana Widya Ardilla (Journal of Urban Society's Arts, 2022)
This research aims to obtain the creation of exploration resulting from the adaptation of the narrative text to the visual book novel Arok Dedes. The method used in this research is applied research, which is to apply basic research for practical purposes, in this case, the design of concept art. Data is collected and compiled by studying libraries related to concept art from textbooks and virtual libraries. The result of this study is that the adaptation of text narrative to visual in concept art requires a comprehensive exploration of starting to develop the concept of space transfer, visual reference, character study, and good mood board. Through the results of this study, it is expected that the exploration of the concept of designing text adaptation to visual concept art can be studied and used as a guide for illustrators who are interested in becoming concept artists, game artists, and character art visualizers. Adaptasi Novel Arok Dedes Karya Pramoedya Ananta Toer dalam Concept Art. Penelitian ini bertujuan untuk mendapatkan konsep penciptaan eksplorasi hasil adaptasi narasi teks ke visual novel Arok Dedes karya Pramoedya Ananta Toer. Metode yang digunakan dalam penelitian ini adalah penelitian terapan, yakni mengaplikasikan penelitian dasar untuk keperluan praktis dalam hal ini perancangan seni konsep (concept art). Data dikumpulkan dan dikompilasi melalui studi pustaka terkait seni konsep baik dari buku maupun pustaka digital. Hasil penelitian ini menyimpulkan bahwa adaptasi narasi teks ke visual dalam seni konsep memerlukan eksplorasi yang komprehensif mulai dari menyusun konsep alih wahana, referensi visual, studi karakter dan mood board yang tepat. Melalui hasil penelitian ini diharapkan eksplorasi konsep perancangan adaptasi teks ke visual seni konsepdapat dipelajari dan digunakan sebagai panduan bagi ilustrator yang tertarik untuk menjadi seniman konsep, seniman gim (game artist) dan pengrajin karakter visual (visualizer art character).